The Effect of Religious Clothing on Gaze Behavior: An Eye-Tracking Experiment. Issue 3 (4th May 2017) - Pazhoohi, Farid; Macedo, Antonio F.; Arantes, Joana
ABSTRACT: There are very few experimental studies regarding religious clothing. In the current study, we hypothesized that the function of conservative clothing hiding female curvaceous body features is to restrict visual access and consequently decreases female physical attractiveness. Using eye-tracking, we quantified dwell times and number of fixations on religious clothing, ranging from conservative to liberal. Results showed that conservative religious clothing decreased visual access to female curvaceous body features and instead focused visual attention to the head/face region. Results were discussed in terms of the roles of conservative clothing in women's clothing choice, men's mate retention tactics, and parent-offspring conflict over mate choice.